Effects of silver nanoparticles on the physiology, stress, and mineral uptake of banana cultivars in vitro and greenhouse - Mendoza N. Natalia; Hidalgo K. Karen; Troya L. Lorena; Sanchez-Timm E. Eduardo; Vielma J. Joel; Venegas M. E. Maria Eulalia; Bogdanchikova N. Nina; Pestryakov A. N. Aleksey Nikolaevich; Chong P. Pablo (2025, 2025)
Title screen